Placenta-Specific Protein 1: A Potential Key to Many Oncofetal-Placental OB/GYN Research Questions - Eric J. Devor; Henry D. Reyes; Donna A. Santillan; Mark K. Santillan; Chinenye Onukwugha; Michael J. Goodheart; Kimberly K. Leslie (Obstetrics and Gynecology International)
Placenta-specific protein 1 (PLAC1) is a secreted protein found in trophoblasts. Several reports implicate a central role for PLAC1 in establishment and maintenance of the placenta. In addition to placentae PLAC1 is expressed in a variety of solids including breast, endometrial, and ovarian cancers. In order to show that PLAC1 is potentially relevant to a number of research questions in OB/GYN, we report on PLAC1 expression in a selected panel that includes two choriocarcinoma cell lines, normal placental tissues, and endometrial and ovarian tumors. We report for the first time that PLAC1 is also expressed in human fetal tissues. PLAC1 is transcriptionally heterogeneous with one promoter (P1) generating two transcripts with alternately spliced 5’ UTRs and the other promoter (P2) generating a third transcript. Placental tissues favor P2 transcripts, while P1 is favored in most of the other cells. Mechanisms determining multiple PLAC1 transcripts and promoter preferences are as yet unknown, but it is clear that this protein is likely to be important in a variety of phenomena relevant to both gynecologic oncology and maternal-fetal medicine.